MINIMALLY INVASIVE INTERVENTIONS IN SURGICAL TREATMENT OF ACUTE PANCREATITIS - Vivek Selvapriya, Yunusova Guzal Fayzullaeva (Research Focus International Scientific Journal, 2025)
The paper analyzes clinical material based on the results of a comprehensive examination and treatment of 102 patients with acute pancreatitis complicated by enzymatic peritonitis, who underwent laparoscopy in the first 72 hours from the onset of the disease. The clinical comparison group included 42 patients with an edematous form of acute pancreatitis. A total of 144 patients (men - 90, women - 54), average age 53.6±3.4 years.